Compaction and Collapse Characteristics of Dune Sand Stabilized with Lime-Silica Fume Mix (2016)
The purpose of this research is to assess the suitability of dune sands as construction materials. Moreover, such a goal is considered beneficial in determining appropriate methods for soil stabilization or ground improvement and to assessing the suitability of dune sands as subgrade layer for carrying roads and rail foundation. Dune sand samples were collected from a region in Baiji area in Salah-Aldeen governorate, North of Iraq. A grey-colored densified silica fume (SF) and lime (L) are used. Three percentages are used for lime (3%, 6%, and 9%), and four rates are used for silica fume (3%, 6%, 9% and 12%) and the maximum percentage of silica fume is mixed with the proportions of lime. Unsoaked California Bearing Ratio (CBR) on compacted dune sands treated dune sands with L-SF by mixing and cured for one day. The increasing in CBR ranged between 443 – 707% at 2.54 mm penetration and 345 – 410% at 5.08 mm penetration.   ResumenEl propósito de esta investigación es evaluar el uso de arena de dunas como materiales de construcción. Además, este objetivo permite determinar los métodos apropiados para la estabilización del suelo, el mejoramiento del terreno y la evaluación de pertinencia de la arena de dunas en capas subbase para carreteras y cimientos férreos. Se recolectaron muestras de arena de dunas en el área de Baiji, del comisionado Salah-Aldeen, al norte de Irak. Se utilizó vapor de óxido de silicio (SF, en inglés), grisáceo y densificado, y óxido de calcio (L). Se utilizaron tres porcentajes para el óxido de calcio (3 %, 6 % y 9 %), y cuatro para el óxido de silicio (3 %, 6 %,  9% y 12%) y el máximo porcentaje del óxido de silicio se mezcló con las proporciones de óxido de calcio. Se realizó en seco el Ensayo de Relación de Soporte de California (del inglés California Bearing Ratio, CBR) en arena de dunas compactada y tratada con la mezcla L-SF curada durante un día. El incremento en el ensayo CBR osciló entre 443-707 % en la penetración de 2.5 mm y 345-410 % en la penetración de 5.08 mm.